1989
DOI: 10.1149/1.2096390
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetics Study of the Atmospheric Pressure CVD Reaction of Silane and Nitrous Oxide

Abstract: A mechanistic study of oxide deposition from silane and nitrous oxide between 495~ and 690~ was performed in a laminar flow, cool wall reactor. Results indicated the existence of two distinct chemical pathways. At high nitrous oxide concentrations, the deposition reaction is dominated by radical chain chemistry initiated by the decomposition of N20. At lovcer N20 concentrations, the decomposition of siIane to form silylene (SiH~) initiates the deposition. Studies of the reaction of disilane and nitrous oxide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Previous studies of SiO 2 formation from SiH 4 and N 2 O using atmospheric pressure CVD ͑APCVD͒ have reported that both H 2 and H 2 O are plausible reaction products at temperatures from 495 to 690°C. 16,17 Under the low pressure RTCVD conditions employed here, the formation of H 2 is the dominant ͑by Ͼ100ϫ͒ if not exclusive reaction channel for the deposition of SiO 2 , a result confirmed under both static and regular process conditions. The lower pressures employed in the RTCVD process are expected to enhance surface processes ͑e.g., as compared to gas phase reactions found more commonly at APCVD conditions͒.…”
Section: B Process Chemistry In Cvd Oxide Growthsupporting
confidence: 63%
“…Previous studies of SiO 2 formation from SiH 4 and N 2 O using atmospheric pressure CVD ͑APCVD͒ have reported that both H 2 and H 2 O are plausible reaction products at temperatures from 495 to 690°C. 16,17 Under the low pressure RTCVD conditions employed here, the formation of H 2 is the dominant ͑by Ͼ100ϫ͒ if not exclusive reaction channel for the deposition of SiO 2 , a result confirmed under both static and regular process conditions. The lower pressures employed in the RTCVD process are expected to enhance surface processes ͑e.g., as compared to gas phase reactions found more commonly at APCVD conditions͒.…”
Section: B Process Chemistry In Cvd Oxide Growthsupporting
confidence: 63%
“…When large ratios of N 2 O and Si 2 H 6 are subjected to LPCVD conditions, it has been suggested that Si and SiO are codeposited, with SiH 2 contributing to Si deposition 404 . It has been suggested that the species believed to be responsible for SiO deposition, the elusive parent silanone H 2 SiDO, is formed from SiH 2 (equation 120) 405 .…”
Section: Silylene Intermediates In Chemical Vapor Depositionmentioning
confidence: 99%
“…Silane (SiH 4 ) is a specialty gas widely employed in the semi-conductor and electronic component manufacturing industry [1]. Mixed with an oxidant such as nitrous oxide (N 2 O), silane can lead to the formation of insulating thin films of silicon oxide which protect the semi-conductors and electronic components [2]. Several studies on SiH 4 -N 2 O mixtures have mainly focused on the silica film growth rate under chemical vapor deposition conditions [2,3].…”
Section: Introductionmentioning
confidence: 99%